The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3928/00220124-20210514-09
|View full text |Cite
|
Sign up to set email alerts
|

Coming of Age During Coronavirus: New Nurses' Perceptions of Transitioning to Practice During a Pandemic

Abstract: Background: The global COVID-19 pandemic has created unprecedented challenges to the health care workforce. Little is known about the effect of the pandemic on new RNs and their preparedness for such a crisis. This study explored the lived experiences of RNs transitioning from students to professionals during the pandemic. Method: Semistructured interviews were conducted with 15 new RNs working in acute care facilities during the Maryland COVID-19 State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 18 publications
3
31
0
1
Order By: Relevance
“…Whether it was experienced more intensely than previous years seems likely due to limited preparation for what they were introduced to upon entrance to practice. 4 , 9 Further elucidations on this question can be expected as new research on the experiences of nurses with and without experience during the pandemic continues to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether it was experienced more intensely than previous years seems likely due to limited preparation for what they were introduced to upon entrance to practice. 4 , 9 Further elucidations on this question can be expected as new research on the experiences of nurses with and without experience during the pandemic continues to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This study found anxiety, depression, and posttraumatic stress disorder in some of the interviewees and suggests nursing educators may benefit from incorporating psychological interventions into nursing education curriculum. Another qualitative study by Sessions et al 4 investigated new nurses' experience in a similar timeframe caring for COVID‐19 patients in a hospital setting. Similar themes emerged including uncertainty, vulnerability, and resilience.…”
Section: Vulnerable New Graduate Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no assessments have been performed on the quality of clinical environments to maximise the clinical competences achieved [ 11 , 12 ]; also, new clinical tutors have been appointed without any training [ 13 ], and the continuity of the clinical experience has not always been ensured, due to the continuous changes in the mission of units and episodes of isolation or quarantine [ 14 ]. Furthermore, only limited transition programmes have been offered [ 15 ] to help new graduates to enter their first working environments using supervision and peer support in good clinical settings [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Siendo el apoyo psicológico a las enfermeras una acción favorable para contar con un personal apto emocionalmente para ejercer sus funciones óptimamente 5 . 6 comentan que las nuevas enfermeras necesitan un mayor apoyo durante la transición a la práctica. Las iniciativas para mejorar las relaciones de confianza entre las nuevas enfermeras y sus organizaciones y el apoyo al desarrollo de relaciones esenciales, siendo esta una labor fundamental por parte de la gerencia.…”
Section: Resultsunclassified